Intra-seasonal variation of anthropometrical, conditional, and technical tests in U14 soccer players - Francioni, F. M.; Figueiredo, A. J.; Lupo, C.; Terribili, M.; Condello, G.; Tessitore, A. (Revista Internacional de Ciencias del Deporte, 2018)
This study aimed to analyze the annual variation of soccer players abilities assessed by means of a field-battery test administered six times during an entire competitive season (from T0 to T5). Anthropometric (i.e., body mass, stature, and body mass index), soccer skill (i.e., touch with the body, touch with the head, passing, shooting, dribbling with pass, and dribbling) and functional capacities (i.e., counter-movement jump with and without free arms, and speed) tests were submitted to 33 Under-14 soccer players. A general improvement across the season as confirmed by the rising effects from 0.3 (T2) to 0.6 (T5) was showed. The technical skills (except touch with the head and dribbling) and functional tests showed significant differences (p < 0.001) between T0 and T5 but they were not dependent by the exposure to training. This study underlined that the skills` development in youth soccer players are not linear due to the effects of the growth and maturation. In order to optimize this process, in-season assessment are needed. Finally, programs and decisions promoted by coaches and scouts aimed to the development of youth soccer players should be inspired by the potential results that might be achieved by players.